2008
DOI: 10.1534/genetics.107.086306
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Sex-Linked Effects on Transcription Regulation As Revealed by Expression Quantitative Trait Loci Mapping in Lake Whitefish Species Pairs (Coregonus sp., Salmonidae)

Abstract: Mapping of expression quantitative trait loci (eQTL) is a powerful means for elucidating the genetic architecture of gene regulation. Yet, eQTL mapping has not been applied toward investigating the regulation architecture of genes involved in the process of population divergence, ultimately leading to speciation events. Here, we conducted an eQTL mapping experiment to compare the genetic architecture of transcript regulation in adaptive traits, differentiating the recently evolved limnetic (dwarf ) and benthic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 93 publications
(98 reference statements)
4
83
1
Order By: Relevance
“…In whitefish, a recent eQTL analysis of muscle tissue that used the same backcross individuals used in our study revealed that 21% of transcripts were differentially expressed between males and females . In addition, our observation of significantly more eQTL in males than in either the female-only or combined data set provides additional support for the results of Derome et al (2008), which observed divergence in the genetic architecture of gene expression between sexes. Together, these studies suggest that sex-biased genetic architecture of transcription may be an important component of evolutionary divergence in whitefish.…”
Section: Discussionsupporting
confidence: 76%
“…In whitefish, a recent eQTL analysis of muscle tissue that used the same backcross individuals used in our study revealed that 21% of transcripts were differentially expressed between males and females . In addition, our observation of significantly more eQTL in males than in either the female-only or combined data set provides additional support for the results of Derome et al (2008), which observed divergence in the genetic architecture of gene expression between sexes. Together, these studies suggest that sex-biased genetic architecture of transcription may be an important component of evolutionary divergence in whitefish.…”
Section: Discussionsupporting
confidence: 76%
“…(b) Gene expression and genome scan in natural populations We used gene expression data obtained from the analysis of white muscle [35] and whole brain [34] tissues. Briefly, these studies used microarrays and the linkage map of Rogers et al [32] to localize eQTL of genes expressed in white muscle (262 transcripts localized) and brain (249 transcripts localized) for one of the backcross family (BC D map).…”
Section: Methods (A) Genetic Mappingmentioning
confidence: 99%
“…Combining both QTL and genome scan information revealed that a total of six eQTL regions co-localized with pQTL and were also outliers in a genome scan study [31,33]. Moreover, these genomic regions were nonrandomly distributed across the genome and hinted at the role of major regulatory hotspots controlling the expression of numerous genes [34,35].…”
Section: Methods (A) Genetic Mappingmentioning
confidence: 99%
“…A total of 48 loci with an average of 14 loci per lake showed restricted gene flow relative to neutral expectation, suggesting a role of directional selection on their divergence. Further insight into the identity of these 'anonymous' AFLP markers was gained by combining information obtained from population genomics with that of pQTL and eQTL mapping Derome et al 2008;Whiteley et al 2008). Thus, homology between markers used in mapping and population genomics was found for 180 markers and for 24 of the 48 outlier loci.…”
Section: Finding Evidence For Natural Selection At the Genome Level Imentioning
confidence: 99%